Exploring the root causes of academic stress among undergraduate students in Durban, South Africa - Khumalo, S. (South African Journal of Higher Education, 2026)
The conditions being faced by university students have deteriorated, while the institutions of higher learning are enrolling a massive number of undergraduate students. This article looks at factors that make undergraduate students suffer from academic stress, which leads to their underperformance and not focus on completing their degrees on time. The theoretical framework used was narrative therapy and ecosystems perspective to connect the researcher to the existing knowledge. Data were collected using in-depth semi-structured interviews. Fifteen undergraduate students were sampled, utilising convenience sampling. Academic stress does not always have negative consequences but can bring positive outcomes for undergraduate students if it is well managed. A collaborative effort among structures in universities is vital in addressing the negative impact of this phenomenon. This article recommends the skills reinforcement of students, counsellors, lecturers, mentors, and tutors on non-educational methods (such as continuous psychosocial support), which could assist academically stressed students to overcome social challenges that have a negative impact on their academic life: a student-friendly strategy to monitor and assist mischievous students; collaborative engagement among student structures in fighting the stigma of academic stress; the establishment of student support groups; the involvement of students in policy formulations on issues like stress; and broader academic discussions about academic stress. Since empirical evidence on challenges students face at universities and colleges during post-Coronavirus (COVID-19) is inadequate, this article fills that gap.